2009
DOI: 10.1179/174313209x444035
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and clinical prognostic indicators for early hematoma enlargement after spontaneous intracerebral hemorrhage

Abstract: Clear prognostic indicators exist for early hematoma enlargement after spontaneous ICH, suggesting that hematoma inhomogeneity has important implications for predicting ICH progression, and we discovered as well as defined the 'hematoma enlargement border', an imaging characteristic of early hematoma enlargement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 8 publications
0
13
0
2
Order By: Relevance
“…Additional studies have later confirmed this observation (51, 69). The presence of heterogeneity is further linked to mortality and poor functional outcome (68).…”
Section: Non-contrast Computed Tomographymentioning
confidence: 57%
See 1 more Smart Citation
“…Additional studies have later confirmed this observation (51, 69). The presence of heterogeneity is further linked to mortality and poor functional outcome (68).…”
Section: Non-contrast Computed Tomographymentioning
confidence: 57%
“…The hypothesis behind this observation is that the irregularity could result from multiple leaking vessels feeding the hematoma and hence a higher probability of hematoma expansion (70). Even though the observation that irregularity of the hematoma shape should facilitate hematoma expansion is validated in a large study elaborated by Fujii et al (71), other studies have not been able to confirm this finding – thus making irregular shaping of the hematoma an uncertain predictor of hematoma expansion (48, 51, 69). …”
Section: Non-contrast Computed Tomographymentioning
confidence: 98%
“…As well, the occurrence of hematoma growth, which occurs in up to one-third of all ICH patients, is another predictor of poor outcome (Fujii et al, 1994;Ji et al, 2009). On-going bleeding appears to be minimal in the autologous blood infusion model (MacLellan et al, 2008) whereas collagenase infusion causes bleeding that starts within minutes to last for several hours (MacLellan et al, 2008;Rosenberg et al, 1990).…”
Section: Outcome End Pointsmentioning
confidence: 99%
“…Haematoma density heterogeneity could be a substitute for the prediction of haematoma expansion. Haematoma heterogeneity refers to the irregularity of shape and density of the initial haematoma on the CT scan, and researchers have found an association between haematoma heterogeneity and haematoma expansion [13, 81]. Takeda et al [159] concluded that the presence of haematoma volume above 16 mL, haematoma heterogeneity and 1.5 h of a systolic blood pressure above 160 mmHg together increased the likelihood of haematoma expansion to approximately 59 %.…”
Section: Acute Progressing Haemorrhagic Strokementioning
confidence: 99%
“…Takeda et al [159] concluded that the presence of haematoma volume above 16 mL, haematoma heterogeneity and 1.5 h of a systolic blood pressure above 160 mmHg together increased the likelihood of haematoma expansion to approximately 59 %. Although its definition was traditionally arbitrary, Ji et al [81] defined the haematoma heterogeneity as a difference of over 20 HU in CT value between two regions exceeding 10 mm 2 in area. Barras et al used quantitative CT densitometry to measure mean attenuation, square root of variance, coefficient of variation, skewness and kurtosis of the attenuation distribution of the haematoma; they found that the coefficient of variation and the square root of variance, along with the basic haematoma volume, are predictors of greater growth.…”
Section: Acute Progressing Haemorrhagic Strokementioning
confidence: 99%